The Impact of E-Wallet Usage on Millennial Consumer Purchasing Interest (Case Study: OVO and Dana) - Marti Utari; Mardiana; M. Zulkarnain (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The development of digital technology has driven a significant transformation in the payment system, marked by the increasing use of e-wallets among the public, especially millennials. This study aims to analyze the influence of ease of use, security, and promotions on the purchasing intentions of millennials using OVO and DANA e-wallets in Indonesia. Using a quantitative approach and purposive sampling technique, data was collected from 100 respondents who are active e-wallet users. The results of multiple linear regression analysis indicate that the three independent variables have a positive and significant influence on purchasing intentions, with the largest contribution coming from the promotion factor. The R Square value of 0.678 indicates that the model is able to explain 67.8% of the variability in consumer purchasing intentions. These findings reinforce the importance of ease of use, security, and effective promotional strategies in increasing e-wallet usage and user loyalty, especially among the millennial segment.